2015
DOI: 10.3844/ajidsp.2015.41.47
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Multi-Drug and Metal Resistant Aeromonas Species from Diverse Sources

Abstract: Abstract:The abuse of antibiotics in the modern era, lead the microorganisms to develop resistance. Antibiotic resistance becomes the part of natural selection in bacteria which allows them to survive in different environments. Bacteria like Aeromonas are able to adapt to changes in the environment such as an increase in antibiotic concentration, which often results in the development of mutations allowing them to survive in unfavourable conditions. The origin of antibiotic resistance in the environment is rel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…A recent study, however, showed a high frequency of silver-resistant genes in endodontic bacteria ( 22 ). Notably, over the past few decades, the coselection phenomenon of ARGs and MRGs frequently has been observed in a variety of environments ( 23 , 24 ). Heavy-metal pollution in the natural environment can play a significant role in maintaining and enhancing antibiotic resistance ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…A recent study, however, showed a high frequency of silver-resistant genes in endodontic bacteria ( 22 ). Notably, over the past few decades, the coselection phenomenon of ARGs and MRGs frequently has been observed in a variety of environments ( 23 , 24 ). Heavy-metal pollution in the natural environment can play a significant role in maintaining and enhancing antibiotic resistance ( 25 28 ).…”
Section: Introductionmentioning
confidence: 99%
“…At sites characterized by both high antibiotic and metal burden, such as soil and water impacted by agriculture and aquaculture, coselection has frequently been observed (Ji et al, 2012;Seiler and Berendonk, 2012;Zhu et al, 2013). Moreover, the coselection phenomenon has been exemplified in the bacterial communities inhabiting the human body (Davis et al, 2005;Amsaveni et al, 2015). Another challenge faced by the public for antibiotic and metal resistance coselection is the cotransfer of ARGs and MRGs via MGEs (mobile gene elements), which has been realized in various habitats, such as human gut (Broaders et al, 2013;Ma et al, 2016), animal gut and impacted soil (Johnson et al, 2016;Losada et al, 2016), sediment (Rosewarne et al, 2010) and sludge (Gaze et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, the co-selection of resistance genes with genes coding for other characteristics has occurred, for example, such is the case for heavy metal tolerance genes [15] 2 of 12 and virulence genes [16]. Co-selection of antibiotic resistance with heavy metals has already been observed in metagenomic samples as in animals [17,18], soils [19], water [20], and also at the genomic level, for instance, in bacteria of the genus Aeromonas [21] and Vibrio parahaemolyticus [18].…”
Section: Introductionmentioning
confidence: 99%